Analisis Hubungan Tingkat Pengetahuan Terhadap Perilaku Swamedikasi Obat Analgesik-Antipiretik Masyarakat Desa Yosowilangun Gresik - Resti Nur Farida Hariyono; Ahmad Suriyadi Muslim; Fahrudin Arif (Universitas Respati Indonesia, 2026)
Self-medication is a common practice used by the public to manage minor health complaints, such as fever and pain, by using over-the-counter analgesic and antipyretic medications that can be obtained without a prescription. Convenience, accessibility, and lower costs are the main reasons for choosing self-medication. However, improper use of medications may occur if individuals lack adequate knowledge regarding the type, dosage, purpose, and proper use of drugs. This study aimed to analyze the relationship between the level of public knowledge and self-medication behavior in the use of analgesic and antipyretic drugs among residents of Yosowilangun Village, Gresik Regency. This study employed a quantitative correlational design with a cross-sectional approach. The population consisted of 12,667 residents, and a sample of 100 respondents was selected using the Slovin formula. Data were collected through validated and reliable questionnaires and analyzed using univariate analysis and the Chi-Square test. The results showed that most respondents had a good level of knowledge (73%) and good self-medication behavior (91%). Statistical analysis revealed a p-value of < 0.001, indicating a significant relationship between the level of public knowledge and self-medication behavior in the use of analgesic and antipyretic medications